2021
DOI: 10.3389/fimmu.2021.739048
|View full text |Cite
|
Sign up to set email alerts
|

The Immunoregulatory Role of the Signal Regulatory Protein Family and CD47 Signaling Pathway in Type 1 Diabetes

Abstract: BackgroundThe pathogenesis of type 1 diabetes (T1D) involves complex genetic susceptibility that impacts pathways regulating host immunity and the target of autoimmune attack, insulin-producing pancreatic β-cells. Interactions between risk variants and environmental factors result in significant heterogeneity in clinical presentation among those who develop T1D. Although genetic risk is dominated by the human leukocyte antigen (HLA) class II and insulin (INS) gene loci, nearly 150 additional risk variants are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…To better investigate the characteristics of these cells after ITF3756 treatment, we looked at specific genes in each cluster and found the up-regulation of several genes related to the T-cell memory phenotypes ( Figure 7E and Supplementary Table 2 ). Among them Granzyme K, that together with granzyme A was reported to be expressed in an early memory stage of CD8 + T-cells development ( 79 ), the chemokine receptor genes CCR2 and CCR5, CD27 ( 80 ), CD52 ( 81 ), SIRPG ( 82 ) and KLF2 (Kruppel-like factor 2) zinc finger transcription factor expressed on CD8 + T –cells, especially in naïve and memory T-cells, and involved in T-cells trafficking ( 83 ). We also confirmed that ITF3756 treatment showed a reduction of the IFN pathway genes: IRF5, IRF7 and IRF9 were downmodulated and, consequently, also the ISGs IFIT1 and IFIT3.…”
Section: Resultsmentioning
confidence: 99%
“…To better investigate the characteristics of these cells after ITF3756 treatment, we looked at specific genes in each cluster and found the up-regulation of several genes related to the T-cell memory phenotypes ( Figure 7E and Supplementary Table 2 ). Among them Granzyme K, that together with granzyme A was reported to be expressed in an early memory stage of CD8 + T-cells development ( 79 ), the chemokine receptor genes CCR2 and CCR5, CD27 ( 80 ), CD52 ( 81 ), SIRPG ( 82 ) and KLF2 (Kruppel-like factor 2) zinc finger transcription factor expressed on CD8 + T –cells, especially in naïve and memory T-cells, and involved in T-cells trafficking ( 83 ). We also confirmed that ITF3756 treatment showed a reduction of the IFN pathway genes: IRF5, IRF7 and IRF9 were downmodulated and, consequently, also the ISGs IFIT1 and IFIT3.…”
Section: Resultsmentioning
confidence: 99%
“…SIRPG (signal-regulatory protein γ ) is a receptor protein involved in the negative regulation of receptor tyrosine kinase-coupled signaling processes 42 . It has been suggested that SIRPG signaling may play an immunoregulatory role in maintaining peripheral immune tolerance and preventing autoimmunity 43 . In line with existing studies, our analyses demonstrated that SIRPG expression was enriched in T cells and natural killer cells, where blocking of the SIRPG-CD47 interaction has been found to inhibit superantigen-induced T cell proliferation 42, 44, 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Targeting the CD47/SIRP axis has recently become a popular method for tumor treatment, as multiple studies have shown that the expression of CD47 in tumor cells is associated with the expression of various coinhibitory markers (Sharp et al, 2021). In hSIRPα-expressing humanized mice, the synergistic effect of BR105 targeting SIRPα and an anti-CD20 antibody could exert significant antitumor efficacy, supporting the further clinical development of BR105 (Z.-H. .…”
Section: Humanized Mouse Models In Cancermentioning
confidence: 95%